ABO blood group discrepancies: Study of prevalence and related factors - Nepal, Bipin; Shrestha, Bikash; Maharjan, Sabindra; Bhasima, Sunil; Shrestha, Shrawan Kumar (Grande Medical Journal, 2019)
Background: ABO discrepancy is any deviation from the expected pattern of red cell antigen grouping with serum-grouping or when the forward-grouping results do not correlate with reverse-grouping results. This study was done to determine the incidence and causes of ABO discrepancies and to identify the correct blood group for safe blood transfusions. Methods: This is a retrospective descriptive study. It was done on 9970 samples collected between June 2017and May 2018. All ABO typing records kept at the Grande International Hospital (GIH) blood bank laboratory were reviewed. Results: During the study period, 9970 blood grouping tests were performed. ABO discrepancies occurred in 26 of them. Discrepancies were more prevalent in the age of 20-30 and 30-40 years. Majority were seen in patients with history of pregnancy/miscarriage (30%) and with any Carcinoma (23%). The most common blood group involved was B with 34% frequency. 96% were reverse discrepancy type, 84% with extra antibody which was resolved by incubating the sample at 37°C for 30 minutes signifying most probably A and B subgroups and auto/allo antibodies. Conclusion: This study emphasizes the need of considering ABO discrepancies in blood banks for donors and recipients for safe blood transfusion to avoid any fatal complications. This discrepancy ratio of 1/384 is more than in other studied population of other countries and also higher than ABO mismatched transfusion in standard centers in Nepal. Repeat testing and investigating for ABO subgroups and auto/allo antibodies is important.